Belarusians in Lithuanian State Council (1918–1920) (Parliamentary Studies, 2013)
This article shows and analyses Belarusian question in the works of Lithuanian State Council, starting from the very first days of it‘s establishment in the fall of 1917, till the end of it‘s works in the spring of 1920. The main object of research - the Belarusian representation in the Lithuanian State Council (sometimes called Belarusian Secretary or Belarusian fraction), which existed from the 27th of November 1918. Analyse is based on the archival materials, stored in various Lithuanian and Belarusian archives, printed sources, as well Belarusian and Lithuanian press. The first question considered are the circumstances and conditions‘ of Belarusian‘s entry into the Council, formation of their representation in the Council, and it‘s work during the last weeks of 1918. The case of Lithuanian-Belarusian collaboration during the period of early Lithuanian state-bulilding had changed after evacuation of Council and Government to Kaunas during the first days of 1919. Having less impact on the Belarusian ethnic territories, Lithuanian side started to regard Belarusian question more as a factor of foreign policy than it‘s interior affairs. However it was not working actively, Belarusian fraction in the Council still existed, changed its composition in the April of 1919, and together with Ministry of Belarusian Affairs constructed legal representation of Belarusian minority in the country. The author paid attention to the works of representation, positions of it‘s members and their political views on the development of Belarusian-Lithuanian relations.
Keywords: Council of Lithuania; Vilnius Belarusian Rada; Belarusian Secretary; ethnic minorities in Lithuania